PRINSIP NATIONAL TREATMENT HAK KEKAYAAN INTELEKTUAL DALAM PELANGGARAN MEREK ASING MENURUT HUKUM INTERNASIONAL - Ojita Aziziyah; Arif Arif; Sutiarnoto Sutiarnoto (Journal of USU International Law, 2014)
Abstract : In exchange for trade in goods and services, the right brand plays an important role as an element of differentiation between the products with other products as well to be the identity element of the product. High competition and ethical behavior that is not good business to encourage misuse, or forgery even prohibition of such mark. But the era of free trade, and globalization of these constraints must be addressed by each country through various conventions-International conventions in which one of them is the application of the principle of national treatment which demands equal treatment between a product from outside the country from within. In terms of brand, these principles also calls for the abolition of restrictions even desire to also protect foreign brands coming into a country.